Efficient Synthesis of Chiral Trisubstituted 1, 2‐Allenyl Ketones by Catalytic Asymmetric Conjugate Addition of Malonic Esters to Enynes. Issue 5 (22nd December 2015) - Yao, Qian; Liao, Yuting; Lin, Lili; Lin, Xiaobin; Ji, Jie; Liu, Xiaohua; Feng, Xiaoming
Abstract: An N, N′ ‐dioxide/scandium(III) complex catalyzed, highly efficient conjugate addition of malonic esters to enynes is described. A range of trisubstituted 1, 2‐allenyl ketones were obtained in high yields (up to 99 %) with good d.r. (up to 95/5) and excellent ee values (97 %–99 %). Moreover, the products could be easily transformed into chiral furan and 5‐hydroxypyrazoline derivatives, both of which are important skeletons of many biologically active compounds and pharmacologicals. Abstract : An N, N ′‐dioxide/Sc III complex catalyzed conjugate addition of malonic esters to enynes is described. A range of trisubstituted 1, 2‐allenyl ketones were obtained in high yields with good d.r. and excellent ee values. Moreover, the products could be easily transformed to pharmacologically important chiral furan and 5‐hydroxypyrazoline derivatives.